One Health in Agricultural Sectors in Thailand, Lao PDR, and Vietnam: Interconnectedness Between Awareness and Socioeconomic Factors - Pechdin, Watchara; Sinsamphanh, Oulavanh; Bui-Thanh, Long; Naruepatr, Jiraphan; Swangsilp, Sorasich; Chougule, Mahesh; Phrasisombath, Ketkesone; Ho, Tien D. N.; Phan, Van-Phuc (International Journal of Public Health, 2024)
Objective: The study aims to analyze the interconnectedness of farmers' socioeconomic factors and their awareness of the One Health framework. Method: This study conducted a survey with 1,166 observations across Thailand, Lao, and Vietnam and employed binary logit regression for data analysis. Odds ratios were used for interpreting the results. Results: The results indicated that certain socioeconomic factors —particularly household income, age, gender roles within the household, and household size— significantly influenced farmers' awareness and engagement with One Health literacy. Awareness levels varied across the three countries: for example, the composition of adults in Thai farming households was correlated with awareness of environmental health and infectious diseases. In Lao PDR, gender was significantly associated with awareness of animal diseases, while in Vietnam, it was linked to awareness of animal disease transmission. Conclusion: These determinants contribute to the application of a more integrated One Health approach among farmers in these areas.